Pemasaran digital dan minat berkunjung ke Lembang Park and Zoo: Peran content marketing, live streaming, celebrity endorser, dan e-WOM di TikTok - Mila Rosita; Heddry Purba; Lorina Siregar Sudjiman (Journal of Management and Digital Business, 2026)
The popularity of TikTok has made it a dominant digital platform that is strategic for various promotional activities, including those for tourist destinations. This provides opportunities for tourism managers to utilize engaging content marketing, live streaming, the involvement of popular figures as celebrity endorsers, and the dissemination of information through recommendations and reviews (electronic word of mouth) to increase engagement and visit intention among tourists via the TikTok social media platform. This study aims to analyze the influence of content marketing, live streaming, celebrity endorsers, and electronic word of mouth on the visit intention to Lembang Park and Zoo. The study employs a quantitative approach with 170 respondents who follow the Lembang Park and Zoo TikTok account, and analyses the data using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that content marketing, live streaming, celebrity endorsers, and electronic word of mouth positively influence visit intention. These findings imply that tourism destination managers need to integrate these four digital marketing strategies simultaneously, with an emphasis on selecting credible celebrity endorsers aligned with the destination’s image, to effectively build interest in visiting among social media users.